2021
DOI: 10.1007/s43465-021-00541-z
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Reduces Visit Time and Cost of Care for Infants with Developmental Dysplasia of the Hip

Abstract: Background Healthcare institutions and policymakers are searching for system-wide approaches to reduce costs while maintaining quality and improving patient outcomes. In most healthcare systems infants referred for the detecting or treating developmental dysplasia of the hip (DDH) are sent to a radiology department for sonographic evaluation. The total duration of visit and cost of visit are essential variables in any healthcare setting and affect both efficiency and “the bottom line”. By having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…10 The authors' institution also recently performed a separate study which found that POCUS, compared to traditional sonography in the radiology department, led to significantly reduced visit time (42 vs 92 min, p = 0.002) and costs (US$121.13 vs US$339.38, p = 0.002). 19 While this study's findings could likely be extrapolated to traditional sonography, this study's findings add to the growing body of literature that POCUS, when performed by the treating orthopedic surgeon, is a safe, reliable, and costsaving tool in evaluating pediatric orthopedic patients, 12 especially those with DDH. 20 Treatment was started at a mean age of 22 days.…”
Section: Discussionmentioning
confidence: 72%
“…10 The authors' institution also recently performed a separate study which found that POCUS, compared to traditional sonography in the radiology department, led to significantly reduced visit time (42 vs 92 min, p = 0.002) and costs (US$121.13 vs US$339.38, p = 0.002). 19 While this study's findings could likely be extrapolated to traditional sonography, this study's findings add to the growing body of literature that POCUS, when performed by the treating orthopedic surgeon, is a safe, reliable, and costsaving tool in evaluating pediatric orthopedic patients, 12 especially those with DDH. 20 Treatment was started at a mean age of 22 days.…”
Section: Discussionmentioning
confidence: 72%
“…Modern devices allow an immediate point-of-care access, which puts the information clinicians need during the visit, reducing costs and time. 11 Within the time course of our training, we have evolved our method of teaching. Initially, the structure was lecture-based and the next step was to practice on live neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care (POC) medical diagnostics are increasingly utilized in both inpatient and outpatient settings 1 , 2 . The ability to rapidly detect aneurysms, fluid pockets, and other clinical findings that can be managed using an interventional procedure can decrease the time to diagnosis and treatment, leading to improved patient outcomes 3 , 4 . The bedside operation of these POC instruments enables measurement of diagnostic information without the need to transport the patient to a centralized-care facility – reducing cost, time to treat, and in some cases, length of stay 5 .…”
Section: Introductionmentioning
confidence: 99%